Caracterização da criação semi-intensiva de tilápia do Nilo em municípios do noroeste do Rio Grande do Sul - Jovanovichs, Marcos Roberto Casarin (2018)
Continental fish farming is a fast growing food production activity and contributes significantly to the quantity of fish consumed in the world. Due to changes in the population's eating habits and the decrease in fish stocks due to extractivism, the demand for improvements in the management of farming systems becomes a necessity. Fish farming aims to produce fish with good nutritional value for human consumption, also promoting economic and social development for the population. The most produced species in Brazil is the Nile tilapia (Oreochromis niloticus), which presents important productive characteristics, besides a fillet of excellent quality, free of fish bones. In this research the main factors that characterize the productive systems of tilapia in the Northwest region of Rio Grande do Sul, Brazil, were analyzed in the three municipalities with the highest production. The information obtained showed that the semi-intensive system is the one performed by the producers in fishponds and that tilapia farming has been a profitable activity, with a net margin of approximately 24% on average.